INTEGRASI PKL DAN TAMAN LINGKUNGAN - R. Siti Rukayah; Athia Maulida Tsania Shofie (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2023)
Abstract: This paper reveals the integration of street vendors into residential neighbourhood parks. Three street vendors operating day and night. Their existence visually reduces the comfort of neighbourhood parks and housing.Â Previously, designs had been carried out using containers, but shop buildings were chosen because they were cheaper. The residents formalized the street vendors into three small shops. The setback of the building is further back into the garden, so it has parking. This research aims to reveal visual comfort based on survey methods, Google Street View observations and interviews. The findings are an improvement in the visual quality of the residential environment and comfort for buyers.Keyword: Street vendors, park, visualAbstrak: Paper ini menguak integrasi PKL ke dalam taman lingkungan perumahan. Tiga buah PKL yang beroperasi siang dan malam secara visual mengurangi kenyamanan taman lingkungan dan perumahan. Sebelumnya telah dilakukan desain dengan menggunakan kontainer tetapi bangunan toko menjadi pilihan karena lebih murah. Warga melakukan formalisasi PKL menjadi tiga buah toko kecil. Setback bangunan lebih mundur ke dalam taman sehingga memiliki ruang parkir yang cukup. Tujuan penelitian ini adalah menguak kenyamanan visual berdasarkan metode survei, pengamatan google street view dan wawancara. Hasil temuan adalahÂ peningkatan kualitas visual lingkungan perumahan dan kenyamanan bagiÂ pembeli.Kata Kunci: PKL, Taman, Visual